Holistic Marketing of Software Products : The New Paradigm - Nigam, Ashutosh (Journal of Commerce and Trade, 2011)
The software product firms needs to be competent in offering services with ever changing demands of the dynamic marketing environment. To overcome these barriers, the firms should focus on holistic marketing strategy based business processes to establish niche markets for their specialized products. Holistic marketing embraces all aspect of firm, software product and measure of usage of software product. The concept stresses on the interrelationship with the stakeholders to achieve distinction with core focus towards the customer requirements.